A versatile valving toolkit for automating fluidic operations in paper microfluidic devices1. Issue 6 (21st March 2015) - Toley, Bhushan J.; Wang, Jessica A.; Gupta, Mayuri; Buser, Joshua R.; Lafleur, Lisa K.; Lutz, Barry R.; Fu, Elain; Yager, Paul
<x xml:space="preserve">Abstract</x> A versatile, powerless, valving and automation toolkit for paper microfluidic devices that uses absorbent expanding elements as actuators is presented.